TRADITION AND MODERNITY IN KABARDIAN MATERNITY CULTURE - Tekueva, Madina Anatol'evna; Nal'cikova, Elena Aniuarovna; Konovalov, Andrej Anatol'evic; Gugova, Marina Habasovna (History, Archeology and Ethnography of the Caucasus, 2024)
This article examines elements of the maternity culture among the Kabardians in contemporary society. It analyzes diverse cases, including older respondents’ accounts of traditional practices and younger women’s innovative experiences regarding this subject. The study incorporates the author’s field materials collected over several years from villages and towns in Kabardino-Balkaria. The selected evidence includes ethnographic information about previously hidden aspects of private female life, specifically pregnancy, childbirth, and the early infancy. Employing participant observation and a phenomenological approach, this research gives voice to women, acknowledging their subjectivity and allowing them to express deeper aspects of consciousness. While existing literature primarily focuses on general attitudes towards young mothers and first-year rituals, this study addresses the research gap by exploring previously neglected aspects of the natal cycle in scientific discourse. It provides a rich ethnographic description of women’s attitudes towards pregnancy and childbirth, including their expectations, disappointments, anxieties, and hopes. The study identifies elements of traditional rural obstetric practices, arguing that modern society exhibits two concurrent processes: the erosion of traditional attitudes in maternity culture and the preservation of some traditional elements. Both the consistencies of everyday culture and their temporal variations are explored.